ANALISIS PESAN DAKWAH PADA AKUN INSTAGRAM @Si_Bedil PERIODE 2021 – JANUARI 2022 - Mochamad Renaldi; Suhendra; Muhammad Fahri (Universitas Pahlawan Tuanku Tambusai, 2022)
In Islam, proselytizing can be interpreted as inviting or calling people to the way of Allah in accordance with Islamic law. The istagram account si_bedil, is an account that conveys proselytizing in the form of it on social media on Instagram. The purpose of this study was to find out the proselytizing messages contained on the si_bedil Instagram account during the period from January 2021 to January 2022. In this study, the research method used was qualitative research. Denzin and Lincoln. revealed that qualitative research is research that uses a natural background to make interpretations of phenomena that occur and involve various existing methods. The results of this study found that in the posts of si_bedil isntagram accounts during the period from January 2021 to January 2022, totaling 65 posts, there were proselytizing messages, 12 uploads of akidah messages, 20 sharia messages and 33 moral messages. In the ungahan also found as many as 32 themes and two methods of proselytizing, namely the method of al-mauidzah hasanah and al- hikmah and in the delivery of the message were found elements of microstructure, setting, detail, presupposition, expression and coherence. Keywords: Da’wah, Instagram, Islamic Comics, Si_Bedil.